2020
DOI: 10.1017/s0022029920000874
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of polypyrrole nanoparticles and aqueous extract ofMoringa oleiferaagainstStaphylococcusspp. carriers of multi-drug efflux system genes isolated from dairy farms

Abstract: Our objectives were to identify genes of the multi-drug efflux system and to evaluate the antimicrobial activities of polypyrrole nanoparticles (PPy-NPs) and aqueous extract of Moringa oleifera against Staphylococcus spp. isolated from dairy farms in Northeast Brazil. Initially, 162 Staphylococcus spp. isolates were subjected to in vitro antimicrobial sensitivity tests. Of these, 35 presented antimicrobial multi-drug resistance phenotypes. These 35 isolates were then referred for the detection of norA, norB, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The bacterial efflux pump is another significant mechanism of antibiotic resistance, which is a major determinant of intrinsic and/or acquired resistance [ 7 ]. Silva et al [ 27 ] reported the presence of norA , norC , tet38 , and msrA genes in their S. aureus isolates. According to these results, isolates with molecular mechanisms of resistance to quinolones (e.g., norA and norC genes), tetracyclines (e.g., tet38 gene), and macrolides (e.g., msrA gene) circulated in their studied farms, and these genes can play a role in multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial efflux pump is another significant mechanism of antibiotic resistance, which is a major determinant of intrinsic and/or acquired resistance [ 7 ]. Silva et al [ 27 ] reported the presence of norA , norC , tet38 , and msrA genes in their S. aureus isolates. According to these results, isolates with molecular mechanisms of resistance to quinolones (e.g., norA and norC genes), tetracyclines (e.g., tet38 gene), and macrolides (e.g., msrA gene) circulated in their studied farms, and these genes can play a role in multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression of norC is also found to be up-regulated during S. aureus biofilm growth [ 28 ]. The tet38 gene can help with the extrusion of antibiotics and can also support the survival and replication of staphylococci inside the host cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial behavior of soluble polypyrrole against S. aureus isolates from mastitis cases has also been evaluated in previous studies, with satisfactory results characterized by low Minimum Inhibitory Concentration (MIC) values (ACOSTA et al, 2020;SILVA et al, 2020). From this perspective, this study aimed to evaluate the efficacy of an intramammary formulation based on soluble polypyrrole in cows affected by experimentally induced mastitis caused by S. aureus.…”
Section: Microbiologymentioning
confidence: 99%
“…A number of studies have already verified the in vitro antimicrobial activity of polypyrrole against S. aureus isolates (ACOSTA et al, 2020;SILVA et al, 2020). However, it is well known that in vitro antimicrobial activity does not imply in vivo efficacy since drug action within bovine mammary glands depends on various pharmacokinetic characteristics of the formulation tested (PYÖRÄLÄ, 2009).…”
Section: Alves Et Almentioning
confidence: 99%